Methodology of Control and Evaluation of cooperative Studies of Future Kindergarten Teachers and Music Tutors in Forming Their Musical-Pedagogical Competence - Savchenko, Rehina (Pedagogical Discourse, 2014)
Methodology of control and evaluation of cooperative studies in forming musical-pedagogical competence of the future kindergarten teachers and music tutors of preschool educational establishments is reflected in the article. The levels of evaluation of knowledge, abilities, skills of the future kindergarten teachers and musical tutors in cooperative studies are determined – high, middle, low, according to the parameters that included also the evaluation of professionally meaningful qualities of the future specialists. It is found out, that in the process of evaluation of group educational results the balance of individual and command interests and achievements should be followed, that must be reflected in percent correlation of group and individual evaluation. The attention is concentrated on difficulties of communicative character that arise in the process of cooperative studies and ways of their overcoming due to the mastering four levels skills.